Loss of Appetite in Adult Patients: Effectiveness and Safety of an Appetite Stimulating Medication in an Open-Label, Investigator-Initiated Study in India - S. Nagaraj (Journal of Nutrition and Metabolism)
Loss of appetite (LOA) may have a negative impact on a patient’s well-being owing to loss of nutrition and associated conditions. The current study assessed the effects of an appetite-stimulating medication containing multivitamins, lysine, and zinc in Indian patients with a history of LOA. Using an investigator-initiated, single-center, open-label, single-arm design, we evaluated the effectiveness and safety of the appetite-stimulating medication (15 mL) in 50 male or female patients (18–55 years old) attending the outpatient department, with a confirmed diagnosis of LOA after two weeks of therapy and assessed the change in Council on Nutrition Appetite Questionnaire (CNAQ) score and safety of the medication after two weeks of treatment. CNAQ scores were presented as mean (standard deviation (SD)). The mean age of patients was 42.1 years, with the majority (66%) being males. At weeks 1 and 2, a statistically significant improvement was observed in the mean CNAQ scores of 25.48 (5.10) and 25.48 (4.29), respectively, vs. baseline (22.08 (2.76); P ≤ 0.0001 both). Majority of the patients had CNAQ appetite scores of 17–28 at baseline (94%), week 1 (66%), and week 2 (78%) of treatment. For patients with acute and chronic illness, a statistically significant improvement was observed in the mean CNAQ score at week 1 (26.75 (3.69), P = 0.0256; 25.24 (5.33), P = 0.0004) and at week 2 (26.63 (3.46), P = 0.0027; 25.26 (4.43), P ≤ 0.0001) from baseline (21.88 (3.31) and 22.12 (2.69), respectively). No serious adverse events were reported during the study. The study findings suggest that appetite-stimulating medication containing multivitamins, lysine, and zinc could be a suitable treatment option for the management of LOA with no significant safety concerns.